2008
DOI: 10.1007/s10620-008-0504-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute Deterioration of Idiopathic Portal Hypertension Requiring Living Donor Liver Transplantation: A Case Report

Abstract: Word count: 1,531 words 2 Key words: idiopathic portal hypertension, liver transplantation 3 AbstractCase reports of severe IPH requiring liver transplantation are very rare. We report the case of a 65-year-old woman who was diagnosed as having idiopathic portal hypertension (IPH). At the age of 60 years, her initial symptom was hematemesis due to ruptured esophageal varices. Computed tomography of the abdomen showed splenomegaly and a small amount of ascites without liver cirrhosis. She was diagnosed as havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…IPH rarely results in neither end-stage liver failure nor requiring liver transplantation. Past case reports for severe IPH requiring liver transplantation were summarized in Table 1 [ 3 , 5 , 9 , 14 20 ]. To date, about 50 cases of liver transplantation have been reported for IPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IPH rarely results in neither end-stage liver failure nor requiring liver transplantation. Past case reports for severe IPH requiring liver transplantation were summarized in Table 1 [ 3 , 5 , 9 , 14 20 ]. To date, about 50 cases of liver transplantation have been reported for IPH.…”
Section: Discussionmentioning
confidence: 99%
“…Although most IPH patients have a good prognosis with the treatment for esophageal varices and/or other complications due to portal hypertension, some develop end-stage liver failure and need for liver transplantation [ 3 5 ]. It has been reported that about 6% of patients with IPH required liver transplantation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%